2018
DOI: 10.1097/pts.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Patient Safety Culture in the Primary Health Care Corporation – Qatar

Abstract: Objectives: Primary Health Care Corporation (PHCC) is the public primary health care provider in Qatar. Having a patient safety culture (PSC) is the keystone to enabling a continuous process to improve the quality of services and to reduce errors. The objective of this study was to assess the impact of accreditation, quality improvement trainings, and patient safety (PS) trainings on the improvement of the PSC at the PHCC in Qatar. Methods:The Medical Office Survey on Patient Safety Culture from the Agency for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 17 publications
(36 reference statements)
1
6
0
17
Order By: Relevance
“…We used the validated Slovenian version of MOSOPS (15). MOSOPS enables the measurement of patient safety culture at the primary level of healthcare, the detection of possible differences, assistance in understanding the safety of a particular organization, and an evaluation of the impact of specific interventions for improving patient safety culture (16)(17)(18)(19)(20)(21). The survey seeks the opinion of healthcare professionals about 38 items in 10 different dimensions (domains C, D, E and F).…”
Section: Toolsmentioning
confidence: 99%
“…We used the validated Slovenian version of MOSOPS (15). MOSOPS enables the measurement of patient safety culture at the primary level of healthcare, the detection of possible differences, assistance in understanding the safety of a particular organization, and an evaluation of the impact of specific interventions for improving patient safety culture (16)(17)(18)(19)(20)(21). The survey seeks the opinion of healthcare professionals about 38 items in 10 different dimensions (domains C, D, E and F).…”
Section: Toolsmentioning
confidence: 99%
“…16 Locally in Qatar, studies assessing patient safety culture have been conducted in the acute and primary care settings These studies reported organisation safety initiatives and changes at the organisational levels are needed to improve patient safety culture in Qatar. 17,18 Community pharmacies are known to be one of the patient's first point of contact with the healthcare system, where pharmacists play an essential role in providing patient care in a safe manner. Patient safety in community pharmacies is portrayed through the provision of optimal therapeutic agents in appropriate doses by pharmacists to meet the health-related needs of patients or customers.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] In spite of considerable advances in healthcare technology and skills of pharmacists over the past decades, patients in the Arab world are still at risk of being exposed to harm from medication errors as a result of inadequate patient safety cultures within healthcare organisations. 16,17 In Qatar, most of the research and initiatives related to patient safety have occurred in hospital and primary healthcare settings. There is paucity of information and research on community pharmacies' involvement in issues related to patient safety such…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo que avaliou desafios de trabalhar em equipe na APS mostrou que a equipe multiprofissional percebeu a comunicação aberta como um aspecto facilitador do trabalho, e necessita ser realizada de forma direta, sincera, respeitosa e colaborativa, mesmo com divergência de ideias entre os profissionais. A forma de estreitar relações e favorecer a comunicação aberta no cotidiano de trabalho é por meio das reuniões de equipe, as quais são vistas como momentos de integração e construção para um ambiente de trabalho harmonioso, ocasião para estreitar as relações entre a equipe e o planejamento das ações (18) .…”
Section: Resultsunclassified